Study on Highly Active Anti- Retroviral Therapy: prescription pattern and side effects - Sapkota, Sujata; Shakya, Rajani; Pandey, Basudev (Journal of Nepal Pharmaceutical Association, 2012)
Since the introduction of Highly Active Anti Retroviral therapy (HAART) by World Health Organization in 1996, it has been the employed method of drug use in HIV management. Involvement of multiple drugs in the regimen, has also invited multiple complications and side effects is one of them. High chances of occurrence of side effects has called for the need of proper identification and therapy management tools for each HAART user and has highlighted the importance of individualized drug therapy. The aim of the study the prescription pattern of the HAART regimen; frequency of regimen change and its major causes; and the side- effects from HAART. The study was conducted in the ART Clinic of SukraRaj Tropical & Infectious Disease Hospital, Teku. 109 patients, who came to the clinic to refill their prescription, were interviewed by the researcher. After interview, medication file of each patient was reviewed to study the prescribed drug regimen, drug changes and identified reasons for the drug change (as identified by the physicians and recorded in patient medication file); reported side effect experience and laboratory reports were analyzed to study the effect of the HAART regimen on hemoglobin and Alanine Aminotransferase enzyme. The study revealed that the most prescribed HAART regimen constituted a combination of Zidovudine, Lamivudine and Nevirapine. 52% of the patients reported having experienced side effects from HAART. 23.85% patients had to have their initial regimen changed because of drug toxicity. Nausea (15.6%), vertigo (14.7%), decreased hemoglobin (11.9%), skin rash/ allergy (9.2%) were the major side effects experience reported by the patients. In addition to some side effects like nausea, vertigo etc; decrease in the level of hemoglobin after the initiation of HAART was evident. Decrease in Zidovudine containing regimen, during the regimen change was apparent and was mostly related to its hemoglobin lowering activity. DOI: http://dx.doi.org/10.3126/jnpa.v26i1.6630 JNPA. XXVI(1) 2012 12-18